Systematic Review for Collaborative Problem Based Learning Models to Improve Creative Thinking Skills. - Hidayah, Rusly; Dasna, I. Wayan (SHS Web of Conferences, 2022)
Learning activities become teaching and learning activities that are quite complicated and challenging. As for a learning model that can be applied, namely the collaborative learning (CL) model with problem-based learning (PBL). This model is like providing space in developing students' social skills. Thus, with the initiative of the researcher to conduct a literature study to be able to examine how the influence in learning with the application of the CL and PBL methods. The research carried out applies a systematic meta-analysis approach with various reference articles that are still relevant according to the research topic in the last 10 years. In addition to this, the implementation in the form of collaborative groups is expected to create an exchange process between the ideas possessed by students. Referring to the results of the study through various references, the conclusion obtained is that the learning model with CL combined with PBL allows the teacher and students to share information efficiently and effectively. The implementation of Collaborative Problem Based Learning can optimize the ability to think critically and creatively for students.